2019
DOI: 10.3389/fmicb.2019.01897
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Brucella melitensis in Kazakhstan in Relation to World-Wide Diversity

Abstract: We describe the genetic diversity of 1327 Brucella strains from human patients in Kazakhstan using multiple-locus variable-number tandem repeat (VNTR) analysis (MLVA). All strains were assigned to the Brucella melitensis East Mediterranean group and clustered into 16 MLVA11 genotypes, nine of which are reported for the first time. MLVA11 genotype 116 predominates (86.8%) and is present all over Kazakhstan indicating existence and temporary preservation of a “founde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 42 publications
3
21
0
Order By: Relevance
“…In Asian countries including China, bruce07 and bruce09 in panel 2B loci consistently showed low HGDI values. In most European countries, all loci in panel 2B were highly discriminatory [29]. These data suggested that mutants occurred only in a high (panel 2B) variety of loci, and the pathogens considered in this study might have originated from a recent common ancestor.…”
Section: Discussionmentioning
confidence: 56%
“…In Asian countries including China, bruce07 and bruce09 in panel 2B loci consistently showed low HGDI values. In most European countries, all loci in panel 2B were highly discriminatory [29]. These data suggested that mutants occurred only in a high (panel 2B) variety of loci, and the pathogens considered in this study might have originated from a recent common ancestor.…”
Section: Discussionmentioning
confidence: 56%
“…Genotype 116 is shared by strains from 28 different provinces in northern and southern China, revealing that these strains had a common geographic origin. Genotype 116 is responsible for the vast majority of Brucella infections in humans and animals [28] and is predominant in many countries, accounting for more than 77% of cases in Portugal and Kazakhstan, 37% in Spain, 16% in Turkey, and 10% in France [29]. Many shared MLVA-16 genotypes were observed among strains from northern and southern regions, and three brucellosis epidemic periods.…”
Section: Discussionmentioning
confidence: 99%
“…Kazakhstan is a hyperendemic area, considering the very high incidence rates in the human population and farm animals ( 1 ). From 1999 to 2016, 38,557 new cases of HB were recorded, with annual counts of cases ranging from 1,443 (2014) to 3,596 (2004) ( 8 ). In Pakistan, the high age-wise prevalence was recorded as 32.25% (98/304) by enzyme-linked immunosorbent assay (ELISA) ( P < 0.05) in 21- to 30-year-old females ( 9 ).…”
Section: Introductionmentioning
confidence: 99%